The influence of text segmentation on garden path processing: evidence from self-paced reading and eye-tracking - Andromachi Tsoukala; Margreet Vogelzang; Ianthi Maria Tsimpli (Language and Cognition)
Line breaks are ubiquitous in continuous text, as in this article. Despite this prevalence, their effects on parsing and interpretation have been markedly understudied in previous research on written language processing. To shed light on these effects, we conducted a self-paced reading and an eye-tracking study in which participants read multiline texts that contained direct object–subject ambiguity, a type of temporary clause boundary ambiguity. Within these texts, we manipulated the placement of line breaks so that they either regularly coincided or clashed with clause boundaries. We hypothesised that this manipulation would cause readers to adjust their parsing strategies and interpretative commitments. Results revealed that the way in which text is segmented through line breaks can significantly affect how readers parse syntactically ambiguous structures. While coinciding line breaks and clause boundaries helped readers arrive at the correct analysis of the ambiguous structures, cases of line break and clause boundary clash led readers down the garden path during online processing, and in some cases also impacted their comprehension. Findings are discussed in terms of their implications for the importance of text segmentation in real-world settings, such as books, educational material and digital content.